Free-electron terahertz radiation based on silicon gratings with in-plane waveguide emission - Chen, Zhaofu; Mao, Leilei; Jin, Mengmeng (Frontiers in Physics, 2022)
We present a method utilizing the coupling between a pre-bunched electron beam and a silicon subwavelength grating to generate coherent terahertz waves. The grating that is connected to two opposite-traveling in-plane waveguides functions as a resonator. An example operating around 2 THz shows that, when the velocity and repetition frequency of the electron bunches respectively match the phase velocity and resonant frequency of the Bragg resonance in the grating, the strong electron-wave coupling leads to coherent radiation through the waveguide. The repetition frequency of the electron bunches can be halved by using its second harmonic to match the resonant frequency. This study might offer a potential approach for on-chip terahertz sources.